The Effect Of Motivation, Communication And Job Satisfaction On Employee Performance - Lestari, Yunita Wahyu; Broto, Bayu Eko; Prayoga, Yudi (International Journal of Science, Technology & Management, 2022)
This study aims to explain whether the variables of motivation, communication and job satisfaction on the performance of the Rantau Prapat stone glass employees. This research data obtained through questionnaires and interviews. The analysis used is descriptive quantitative, multiple linear regression analysis, validity and reliability testing and hypothesis testing. The results show that motivation, communication, and job satisfaction have a positive and significant influence on employee performance.